Desain Antena Mikrostrip Segitiga Sama Sisi sebagai Pendeteksi Partial Discharge - Megastin Massang Lumembang; Fajar Pratama Pongsapan (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2025)
Partial discharge (PD) is a phenomenon that can degrade the insulation system of high-voltage equipment. Early detection of PD requires sensors with high sensitivity in the Ultra High Frequency (UHF) range. This study proposes an equilateral triangular microstrip antenna optimized to operate at 2.45 GHz using an FR-4 substrate (εr = 4.4, thickness 1.6 mm). The side length of the triangular patch was calculated to be 42 mm to achieve resonance at the target frequency. Analysis results indicate that the antenna exhibits a Return Loss of less than -10 dB and a VSWR of less than 2 at the operating frequency, fulfilling the requirements for PD detection applications. This design contributes to the development of compact and cost-effective UHF sensors for condition monitoring of high-voltage equipment, and offers an alternative approach to the development of resonant antennas at 2.45 GHz for microstrip antenna-based PD detection systems.